Stulecie urodzin Profesor Marii Goncerzewicz. Poznański okres jej dzialalności kliniczno-naukowej i organizacyjnej - Krawczyński, Marian (Pediatria Polska - Polish Journal of Paediatrics, 2017)
On the occasion of the birth centenary of Professor Maria Goncerzewicz, her biography and organizational and scientific achievements in pediatrics are presented. Her university studies and over 20 years of her professional career took place at Poznań University of Medical Sciences. Her clinical and scientific activity in the area of metabolic disorders, especially PKU, is presented. Many of her publications were dedicated to the interface between clinical genetics and pediatric endocrinology as well as social pediatrics and school medicine. She devoted the remaining years of her work (1976-1997) to the organization and then clinical and scientific development of The Children's Memorial Health Institute in Warsaw, Poland.